Optimalisasi Sistem Akademik Melalui Desain UI/UX: Integrasi Fungsi Fitur Dosen Pada Aplikasi SIAKAD STIMATA Menggunakan Metode Heuristic Evaluations (HE) - Zulkaria Irawan; Mochamad Husni (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2026)
The Academic Information System (SIAKAD) at STIMATA plays a crucial role in supporting academic processes, particularly for lecturers as active users. However, challenges remain, including unintuitive interfaces, limited features, and unclear user role distinctions. This study aims to evaluate the usability of SIAKAD’s interface from the lecturer’s perspective using the Heuristic Evaluation (HE) method. The evaluation involved 22 lecturers who assessed issues based on Nielsen’s 10 usability heuristics. Each issue was rated using a severity scale from 0 to 4. The results revealed several heuristic violations affecting the system’s effectiveness and efficiency. This study provides prioritized improvement recommendations to enhance user experience and support the development of a more responsive and user-centered interface for lecturers